THE EFFECT OF PLAYING WITH LOOSE PARTS ON FINE MOTOR DEVELOPMENT IN PRESCHOOL CHILDREN AT THE KUNCI III YOGYAKARTA - Istichomah; Setyo Retno Wulandari; freasy kora (Sahabat Publikasi Kuu, 2026)
Background: In order to move items, doodle, arrange blocks, cut, and write, people must develop their fine motor skills, which are small muscles like fingers and hands that require dexterity and hand-eye coordination. A game called